A New Method for (4+1) Dimensional Fokas Equation - Demiray, Seyma Tuluce; Bulut, Hasan (E D P Sciences, 2018)
In this paper, modified exp (-Omega(xi))-expansion function method (MEFM) has been tackled for procuring exact solutions of (4+1) dimensional Fokas equation. Hyperbolic function solutions and dark soliton solutions of (4+1) dimensional Fokas equation have been found by means of this method. Moreover, by the help of Mathematica 9, some graphical simulations were given to clarify the behavior of these solutions.
3rd International Conference on Computational Mathematics and Engineering Sciences (CMES) -- MAY 04-06, 2018 -- Final Int Univ, Girne, CYPRUS
Keywords: Traveling-Wave Solutions